Intensive Care Treatment of Pulmonary Embolism: An Update Based on the Revised AWMF S2k Guideline - Janssens, Uwe (Hämostaseologie, 2024)
Acute pulmonary embolism (PE) remains a significant cause of morbidity and requires prompt diagnosis and management. The prognosis of affected patients depends on the clinical severity. Therefore, risk stratification is imperative for therapeutic decision-making. Patients with high-risk PE need intensive care. These include patients who have successfully survived resuscitation, with obstructive shock or persistent haemodynamic instability. Bedside diagnostics by means of sonographic procedures are of outstanding importance in this high-risk population. In addition to the treatment of hypoxaemia with noninvasive and invasive techniques, the focus is on drug-based haemodynamic stabilisation and usually requires the elimination or reduction of pulmonary vascular thrombotic obstruction by thrombolysis. In the event of a contraindication to thrombolysis or failure of thrombolysis, various catheter-based procedures for thrombus extraction and local thrombolysis are available today and represent an increasing alternative to surgical embolectomy. Mechanical circulatory support systems can bridge the gap between circulatory arrest or refractory shock and definitive stabilisation but are reserved for centres with the appropriate expertise. Therapeutic strategies for patients with intermediate- to high-risk PE in terms of reduced-dose thrombolytic therapy or catheter-based procedures need to be further evaluated in prospective clinical trials.
Keywords: pulmonary embolism; critical care; therapeutic thrombolysis; right-sided heart failure